Promising approach for composting disposable diapers enhanced by Cyanobacteria - D. Kusumawati; S. Mangkoedihardjo (Global Journal of Environmental Science and Management)
Disposable diapers have become a complicated matter due to the risk generation to the environment and human health. This study presents a description of disposable diapers characteristics and the success-proven methods used to handle this waste. In many developing countries where an inadequate waste management system occurs, the handling method selection must consider effectivity, the affordable cost, and the end product quality. Despite the diaper composting has successfully conducted in several previous studies, some issues remain for researchers to address. Thus, it requires an improvement so that the system runs effectively and sustainably. This study aimed to determine the possibility of using Cyanobacteria for enhancing the diapers composting. This study gains insights from previous studies using a literature review method, with the year of publication between 2007 to 2020. The focus of the investigation relates to disposable diapers composting and its optimation by cyanobacteria addition. And so as the future prospecting for application and implication to the environment and human life. Cyanobacteria ability to carry out nitrogen fixation, carbon sequestration, ubiquitous in natural habitat, highly adaptive in a wide range environmental condition, can live in the composting system, perform bioremediation, and its application as quality fertilizer, and potentially degrade plastic polymers, spread the expectation to cyanobacteria which associated with its advantages over other microorganisms to enhance the disposable diapers composting. This study highlights the potential utilization of cyanobacteria as an opportunity for copping disposable diapers pollution. The application of compost resulted expected to provide promising-advantages to the environmental sustainability and agriculture. This paper proposes an overarching review of the feasibility in this regard. ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================